ANALISIS PERANAN EFEKTIVITAS DAN KONTRIBUSI PAJAK RESTORAN TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN BADUNG - Galih Wicaksono; Muhammad Nasrulloh Huda (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2022)
Development in an area that is growing rapidly indicates that the area's revenue is quite good in running a progressive government for the prosperity and welfare of its population. Likewise with the effectiveness and contribution of local taxes to Regional Original Income (PAD), one of which is the Restaurant Tax. Restaurant tax is a tax on services provided by restaurants. This type of local tax is one of the boosters of the Regional Original Revenue of Badung Regency. This study aims to determine the effectiveness and contribution of Restaurant Tax to Regional Original Income. The research method is descriptive quantitative, by analyzing how much effectiveness and contribution from 2017-2021 with secondary data through a website managed by the Regional Revenue Agency (Bapenda) of Badung Regency. The results show that the effectiveness of restaurant tax revenues has fluctuated in the last 5 years, but its contribution to PAD is still in the less category.